2008
DOI: 10.1063/1.2836676
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and magnetic properties of Heusler alloy Co2MnSi epitaxial ultrathin films facing a MgO barrier studied by x-ray magnetic circular dichroism

Abstract: The electronic and magnetic states of an epitaxially grown full-Heusler alloy Co 2 MnSi ͑CMS͒ 1.1 nm ͑4 ML͒ thick ultrathin film and a CMS 50-nm-thick film both facing an epitaxial MgO͑001͒ tunnel barrier were element-specifically studied by means of x-ray absorption spectroscopy ͑XAS͒ and x-ray magnetic circular dichroism ͑XMCD͒. The observed XAS and XMCD spectra revealed that both the CMS films were not oxidized. The Co and Mn spin magnetic moments for the 4 ML thick CMS film obtained by applying the sum rul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 24 publications
7
16
0
Order By: Relevance
“…This consideration is consistent with that the spin polarization of Co-rich CMG estimated from the TMR ratio at 4.2 K for CMG/MgO/ CoFe MTJs assuming Jullière's model, P CMG , was as low as 0.74. 6 It was reported that the m spin ͑Co͒ of Co-rich CMS/MgO was 1.16 B for a sample with t CMS = 50 nm, and 1.25 B for a sample with t CMS = 1.1 nm ͑4 ML͒, 43 both being larger than a theoretical value of 1.06 B . 27 The CMS film composition of Co: Mn: Si= 2 : 0.91: 0.93 was Co-rich similar to the Co-rich CMG that we have studied here.…”
Section: Discussionmentioning
confidence: 96%
“…This consideration is consistent with that the spin polarization of Co-rich CMG estimated from the TMR ratio at 4.2 K for CMG/MgO/ CoFe MTJs assuming Jullière's model, P CMG , was as low as 0.74. 6 It was reported that the m spin ͑Co͒ of Co-rich CMS/MgO was 1.16 B for a sample with t CMS = 50 nm, and 1.25 B for a sample with t CMS = 1.1 nm ͑4 ML͒, 43 both being larger than a theoretical value of 1.06 B . 27 The CMS film composition of Co: Mn: Si= 2 : 0.91: 0.93 was Co-rich similar to the Co-rich CMG that we have studied here.…”
Section: Discussionmentioning
confidence: 96%
“…4 In 0.6 is more than that in Ni 2 MnIn in agreement with experiment. This indicates an increased hybridization between Ni 3d and Mn [28][29][30] . These features are considered to be a signature of localized 3d electrons 28,31,32 .…”
Section: Methodsmentioning
confidence: 99%
“…This indicates an increased hybridization between Ni 3d and Mn [28][29][30] . These features are considered to be a signature of localized 3d electrons 28,31,32 . Alternatively, a selective oxidation of Mn atoms can also result in multiplet structures 29,30 .…”
Section: Methodsmentioning
confidence: 99%
“…To date several studies have utilized these techniques to examine the interfacial properties of materials used in MTJs, [16][17][18][19][20][21][22][23][24] and some of them have focused on Heusler-alloy-based MTJs. Electronic and magnetic properties at interfaces have been investigated for various thicknesses in Co-rich Co 2 MnSi 25,26 and Co 2 MnGe 27 thin films. However, so far, element-specific studies of the effects of off-stoichiometry in Heusler-alloy thin films on their electronic and magnetic properties have not been carried out.…”
Section: Introductionmentioning
confidence: 99%